Family Dynamics and Grandparents' Anxiety and Depression in Intergenerational Rearing Families: A Correlational Study - Yang, Chun-Yan; Xu, Hong-Jiao; Liu, Shan-Shan; Wu, Yue-Jing; Long, Yun; Liu, Hong-Sheng; Chen, Yao-Pian; Li, Xia (Frontiers in Psychiatry, 2021)
Background: In China, intergenerational rearing is a ubiquitous phenomenon based on unique national conditions. This study aimed to explore family dynamics in intergenerational rearing families as well as their correlation with older household members' anxiety and depression. Methods: The elderly from intergenerational (n = 141) and non-intergenerational rearing families (n = 266) were investigated using the following scales: the general information questionnaire, Self-Rating Scale of Systemic Family Dynamics, Geriatric Depression Scale, and Self-Rating Anxiety Scale. Results: Scores from the four dimensions (family atmosphere, system logic, individuation, and the concept of disease) of the structure of family dynamics were computed. The comparison of these dimensions scores and the total scores of grandparents' anxiety and depression for the two groups were not statistically significant (p > 0.05). In Pearson's correlation analysis, no significant correlation between the family atmosphere dimension and the total score of the grandparents' depression and anxiety scales was observed. The system logic aspect was negatively correlated with depression and anxiety scale scores. The individual dimension was positively correlated with the anxiety scale scores. The disease concept dimension was positively correlated with depression and anxiety scale scores. Hence, the results were statistically significant. Conclusion: There were no significant differences in terms of family dynamics and risk of anxiety and depression among grandparents between the two family types. The system logic, individuation, and disease concept dimensions were correlated with their anxiety and depression.